PENINGKATAN EKONOMI MASYARAKAT MELALUI BUDIDAYA JAMUR DI DESA KARANGANYAR KABUPATEN MALANG - Faisal Kamarudin; M. Imamul Muttaqin; Nindita Ratry Wulan Pramesty; Aidah Iswari Zharifah; Misbakhul Ilmi (Fakultas Sains dan Teknologi, 2023)
Community empowerment is an activity to increase community participation in meeting the necessities of life and solving problems experienced by the community. In this case the activity was carried out through the Student Work Lecture program (KKM) which is a community service-based activity to increase student empathy for the condition of society and its environment. Group 125 KKM is a group assigned to Karang Anyar Village, Poncokusumo District, Malang Regency. The method used in this service is the PAR participatory action research method, which aims to find out or describe the reality that occurs in society so that the data obtained is truly objective. The criteria determined as subjects of service are those who are involved in the activities carried out and know and understand information related to service. Based on this, the subjects in this service were selected using the following criteria: community activity programs, including worship, education, and the economy, with the results obtained, namely the development and resolution of problems faced by society, including religion, education, and the economy. This KKM not only benefits the community but also the students who carry out the activity program. Keywords: Improving the Economy, Society, Mushroom Cultivation